Healthcare Providers’ Perceptions Around Antimicrobial Resistance: A Qualitative Study From Northwest Syria - Hussam Alkabbani; Maysoon Dahab; Waseem Zakaria; Ahmad Hmeideh; Nasser Almhawish; Nabil Karah; Aula Abbara (Journal of Global Antimicrobial Resistance)
AIM: This study reveals the perceptions of healthcare providers regarding antimicrobial resistance (AMR) in northwest Syria, seeking to offer practical recommendations. BACKGROUND: Protracted armed conflict and the consequent effects on the wider health system present challenges to addressing AMR. This study explored the perceptions of healthcare providers regarding AMR in this setting. METHODS: We used qualitative research methods with in-depth, semi-structured interviews with Syrian healthcare providers in northwest Syria. Purposive then snowball sampling were used to identify key informants. Interviews were conducted in Arabic, transcribed and uploaded to NVivo for analysis. Deductive thematic analysis was conducted to identify the main themes. RESULTS: 17 interviews were conducted; 5 (29%) female, 11 (65%) physicians, and 6 (35%) pharmacists. Emerging themes focused on 1. healthcare providers’ knowledge of AMR and its perceived extent 2. general drivers of AMR 3. conflict and disaster-related drivers of AMR, and 4. Good practice and recommendations. The role of pharmacies (most of which are private) in providing over-the-counter antibiotics, including without prescriptions, was highlighted. For physicians, weak microbiology laboratory infrastructure and concerns about antibiotic failure were noted. Some areas of good practice, which can be built on, were also explored; these included enforcing antimicrobial guidelines and supplies. CONCLUSIONS: This research provides contextualised information about the challenges relating to AMR in northwest Syria from the perspective of healthcare workers. AMR in northwest Syria requires comprehensive approaches to tackle it, preferably coordinated through the Turkey based health cluster with prioritization and collaboration among all actors involved in healthcare.